Dexmedetomidine versus Lidocaine for Hemodynamic Stability During Airway Management in Patients with Traumatic Brain Injury: A Randomized Clinical Trial - Shallahudin; Aswoco Andyk Asmoro; Ristiawan Muji Laksono; Buyung Hartiyo Laksono (HM Publisher, 2025)
Introduction: The profound sympathoadrenal stress response to endotracheal intubation in patients with traumatic brain injury (TBI) presents a significant risk for secondary brain injury by inducing perilous hemodynamic instability. Pharmacological attenuation is critical, yet direct comparative evidence between commonly used agents is lacking. This study aimed to rigorously compare the efficacy of dexmedetomidine, a central sympatholytic, versus lidocaine, a peripheral membrane stabilizer, in maintaining hemodynamic stability during airway management in the TBI population. Methods: In this prospective, randomized, double-blind clinical trial, seventy-one adult patients with TBI (ASA I-III) were allocated to receive either intravenous dexmedetomidine (1 μg/kg over 10 minutes; n=37) or intravenous lidocaine (1.5 mg/kg over 2 minutes, with total infusion time matched to 10 minutes with saline; n=34) prior to a standardized anesthesia induction. The prespecified primary outcome was the change in mean arterial pressure (MAP) from baseline to one minute post-intubation. Secondary outcomes included changes in heart rate (HR) and hemodynamic profiles over 10 minutes. Results: Baseline patient characteristics, including TBI severity, were well-balanced between groups. Both interventions effectively blunted the pressor response, causing a significant decrease in MAP and HR from baseline (p<0.001 for all). The primary outcome, the change in MAP at one minute post-intubation, was not statistically different between the dexmedetomidine and lidocaine groups (-12.8 ± 6.1 mmHg vs. -11.5 ± 5.9 mmHg, respectively; p=0.412). Similarly, no significant differences in HR or MAP were observed between groups at any time point up to 10 minutes post-intubation. The incidence of rescue therapy for hypotension or bradycardia was low and comparable. Conclusion: In patients with TBI, both dexmedetomidine and lidocaine are effective and safe for attenuating the hemodynamic stress of intubation. At the doses studied, neither agent demonstrated clinical superiority, providing clinicians with two valid, mechanistically distinct options. The choice can therefore be guided by the specific clinical context, including desired onset, duration of action, and sedative profile.